2021
DOI: 10.3390/toxins13010040
|View full text |Cite
|
Sign up to set email alerts
|

Common Mechanism for Target Specificity of Protein- and DNA-Targeting ADP-Ribosyltransferases

Abstract: Many bacterial pathogens utilize ADP-ribosyltransferases (ARTs) as virulence factors. The critical aspect of ARTs is their target specificity. Each individual ART modifies a specific residue of its substrates, which could be proteins, DNA, or antibiotics. However, the mechanism underlying this specificity is poorly understood. Here, we review the substrate recognition mechanism and target residue specificity based on the available complex structures of ARTs and their substrates. We show that there are common m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
4
0
2
Order By: Relevance
“…In other members of the R-S-E clade of bacterial ARTs 24 , the residue (ϕ) in the third position in the ADP-ribosylating toxin turn-turn (ARTT) loop motif X-X-ϕ-X-X-E/Q-X-E, forms essential hydrophobic interactions with substrates. Although the corresponding residue (P260) of TcART, sits at the interface to F-actin, it does not interact there with any specific residue or with a hydrophobic patch (Fig 2c, S7f).…”
Section: Resultsmentioning
confidence: 99%
“…In other members of the R-S-E clade of bacterial ARTs 24 , the residue (ϕ) in the third position in the ADP-ribosylating toxin turn-turn (ARTT) loop motif X-X-ϕ-X-X-E/Q-X-E, forms essential hydrophobic interactions with substrates. Although the corresponding residue (P260) of TcART, sits at the interface to F-actin, it does not interact there with any specific residue or with a hydrophobic patch (Fig 2c, S7f).…”
Section: Resultsmentioning
confidence: 99%
“…The glutamic acid residue of this motif, which is a critical catalytic residue in other ARTs, such as diphtheria toxin and PARP-1 13 , is replaced in Arr by an aspartate residue (D84 in Fig. 3 ) 1 , 14 . Here, we observed that this H-Y-[QED] motif is highly conserved in almost all hundreds of Arr sequences analyzed, indicating its importance in Arr activity, and suggesting that these Arr sequences could be functional.…”
Section: Discussionmentioning
confidence: 99%
“…失 [22,23] . 在整个反应过程中, NAD + 被固定在核心区域 形成的疏水裂隙结合口袋中 [24] . 此外, 还有一类在结 构和催化基序上不同, 但依赖NAD + 的脱乙酰化酶-Sirtuin家族, 也具有ART活性, 及一些非经典类型的…”
Section: 细菌Arts的结构特点unclassified